(untitled) (Portuguese Journal of Family Medicine and General Practice, 2003)
Children with a Fever: Parents’ Knowledge and Attitudes Fever is one of the most frequent presenting complaints from parents who take their children to their family doctor or to Casualty. Although parents usually know how to measure and treat fever, they are afraid of it, fearing serious illness or even seizures. Numerous international studies with parents of infants, toddlers, and pre-schoolers, have revealed a widespread concept of "fever phobia" which often leads to aggressive and inappropriate therapeutic measures. In a non-randomised study, 160 parents were surveyed on their knowledge, attitude and fears concerning their children’s fever and its treatment. 76.8% of parents thought a fever was temperature at or higher than 37.5ºC, and treated their child only when temperature reached 38.0ºC (64.3%). Paracetamol was considered to be the first-line drug (89.9%). Night temperature checks (84.3%) and seeking medical care (37.5%) were to do with parents fearing seizure episodes (81.8%). Most parents (66.2%) view health professionals as their main source of information. Greater awareness of parents’ knowledge and attitudes may facilitate communication in community health education programmes. Nevertheless, effort will have to be put into improving the way information is conveyed by health professionals: an adequate definition of fever, its consequences and its treatment.